Transformasi Pendidikan Islam Berbasis Nilai-Nilai Ulul Albab di Era Literasi Digital - Mahfud (Journal Khafi : Journal Of Islamic Studies, 2024)
This article discusses the contextualization of Islamic education from the perspective of Ulul Albab in the era of digital literacy. Ulul Albab education aims to transform Islamic values ​​so that they have a relevant function and can develop in society. This research was conducted by collecting information and data from books, scientific journals, and library references related to Islamic education and the concept of Ulul Albab. The ideal next generation of the nation is an individual who is intellectually intelligent, understands the verses of God, and makes nature a source of knowledge, especially for believers who always remember God in all situations. In the context of digital literacy, *Ulul Albab* education is an effort to improve digital literacy skills as provisions in living life. Ulul Albab education plays a role as a mainstream that drives educational change by developing new ideas and solving problems related to religion, social, and politics. The purpose of this education is to guide children to be able to develop their potential and competence to the maximum, by emphasizing intellectual, moral, spiritual, scientific, physical, and language aspects. The ultimate goal is to achieve complete devotion to God.